A short self-paced submaximal test to monitor endurance cycling fitness - Cusson-Fradet, J.; Domingue, F.; Lajoie, C. (Journal of Science and Cycling, 2023)
Introduction Monitoring the cyclists` responses to training is important for optimizing training and improving cycling performance (Galán-Rioja, Gonzalez-Ravé, González-Mohíno, & Seiler, 2023; Jeffries et al., 2021). However, this process can be costly and time-consuming. Submaximal fitness tests provide a practical alternative to traditional maximal tests, allowing the monitoring of training effects while minimizing disruptions to the athlete's training and competition schedule (Shushan et al., 2022).